2012
DOI: 10.1016/j.icarus.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

A dynamo driven by zonal jets at the upper surface: Applications to giant planets

Abstract: We present a dynamo mechanism arising from the presence of barotropically unstable zonal jet currents in a rotating spherical shell. The shear instability of the zonal flow develops in the form of a global Rossby mode, whose azimuthal wavenumber depends on the width of the zonal jets. We obtain self-sustained magnetic fields at magnetic Reynolds numbers greater than 10 3 . We show that the propagation of the Rossby waves is crucial for dynamo action. The amplitude of the axisymmetric poloidal magnetic field de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
1
9
0
1
Order By: Relevance
“…The structure of the flow shown in Figure c is typical of the patterns induced by a shear instability in a rotating flow [ Kuo , ; Busse , ; Fruh and Read , ; Hollerbach , ; Schaeffer and Cardin , ; Guervilly et al , ]. This instability is generated by rapid changes of the local rotation rate over a short distance.…”
Section: Semiempirical Scaling Lawmentioning
confidence: 96%
“…The structure of the flow shown in Figure c is typical of the patterns induced by a shear instability in a rotating flow [ Kuo , ; Busse , ; Fruh and Read , ; Hollerbach , ; Schaeffer and Cardin , ; Guervilly et al , ]. This instability is generated by rapid changes of the local rotation rate over a short distance.…”
Section: Semiempirical Scaling Lawmentioning
confidence: 96%
“…Neptune and Uranus have strong non-axial multipolar magnetic field components compared with the axial dipole component (Connerney et al 1991;Herbert 2009). These highly nonsymmetric internal magnetic fields (Ness et al 1986(Ness et al , 1989Connerney et al 1991;Guervilly et al 2012), coupled with the relatively fast planetary rotation and the unusual inclination of the rotation axes from the orbital planes, imply that the magnetospheres of Uranus and Neptune are subject to drastic geometrical variations on both diurnal and seasonal timescales. The relative orientations of the planetary spin, the magnetic dipole axes and the direction of the solar wind flow determine the configuration of each magnetosphere and, consequently, the plasma dynamics.…”
Section: Space Weather In the Outer Solar Systemmentioning
confidence: 99%
“…In addition, Goḿez-Peŕez and Heimpel (2007) showed that weakly dipolar and strongly tilted dynamo fields are stable in the presence of strong zonal circulation and when the flow has a dominant effect over the magnetic fields. Guervilly et al (2012) proposed that if some mechanism is able to transport angular momentum from the surface down to the deep, fully conducting region then the zonal motions may influence the generation of the magnetic field. Such zonal jets at the giant planets may exert, by viscous or electromagnetic coupling, an external forcing at the top of the deeper conducting envelope.…”
Section: Magnetosphere-exosphere-ionosphere Coupling In the Uranian Amentioning
confidence: 99%
“…Such zonal jets at the giant planets may exert, by viscous or electromagnetic coupling, an external forcing at the top of the deeper conducting envelope. The model by Guervilly et al (2012) assumes an idealized one-way coupling between the outer and deep regions, assuming a constant (throughout the whole modeled layer) conductivity and ignoring the back reaction of the deep layer onto the outer layer. In order to assess the role of zonal winds in the generation and topology of the magnetic fields of Uranus and Neptune, determination of the compressibility of the layers, of the radial profiles of the electrical conductivity, of the viscosity and of the viscous coupling between electrically insulating and conducting regions, is necessary.…”
Section: Magnetosphere-exosphere-ionosphere Coupling In the Uranian Amentioning
confidence: 99%
See 1 more Smart Citation